Національний та іноземний досвід впровадження податкової амністії: порівняльно-правовий аспект - Токарєва, К. О. (НДІ ПЗІР НАПрН України, 2022)
У статті розглянуто правове регулювання такого інституту, як податкова амністія, в різних країнах світу. Підкреслено, що в кожній державі впровадження такого інституту має свої особливості закріплення та реалізації. При цьому такі особливості зумовлені різними чинниками, приміром, такими як: територіальний та бюджетний устрій держави, модель податкової системи, модель взаємовідносин між уповноваженими та зобов’язаними учасниками податкових відносин та ін. На підставі аналізу правових механізмів податкової амністії в таких країнах, як Туреччина, Німеччина, Люксембург, Італія наголошено на тому, що їх позитивний досвід має вагоме значення для України. Такий підхід обумовлено тим, що майже усі розглянуті країни вже є діючими членами ЄС або ж прагнуть до вступу до такого Союзу. Підкреслено, що їх законодавчі акти спрямовані на економічно-вигідну та адекватну співпрацю між державою та платником податків. Тенденція закріплення досліджуваного інституту на державному рівні є впевненим кроком до детінізації економіки, як для малого, так і великого бізнесу. Розглянуто деякі особливості регламентації податкової амністії в Україні. Зокрема, йдеться про такий вид податкової амністії, як одноразове (спеціальне) добровільне декларування активів фізичних осіб. Наголошено на тому, що вказане декларування характеризується наявністю власного правового механізму. При цьому такий механізм не є тотожним із механізмами податкової амністії в зарубіжних країнах. Підкреслено, що у національному податковому законодавстві України уперше було впроваджено механізм альтернативних ставок збору за одноразове (спеціальне) добровільне декларування активів фізичних осіб. Зазначимо, що така альтернативність нерозривно пов’язана із процедурою розстрочення, яка суттєво відрізняється від традиційного механізму розстрочення податкового боргу платників податків. Problem setting. The article examines the legal regulation of such an institution as tax amnesty in different countries of the world. It is emphasized that in each country the introduction of such an institution has its own peculiarities of consolidation and implementation. At the same time, such peculiarities are due to various factors, for example, such as: the territorial and budgetary structure of the State, the model of the tax system, the model of relations between authorized and obligated participants of tax relations, etc. Analysis of recent researches and publications. Tax amnesty, the prospects for its implementation, and the experience of foreign countries have been the subject of research by such scholars as I. Bezzub, A. Glazova, O. Dmytryk, O. Makukh, I. Prykhodko, O. Slizko etc. The target of the research is to make a comparative legal analysis of the implementation of tax amnesty in the Ukraine and abroad. Article’s main body. Based on the analysis of the legal mechanisms of tax amnesty in such countries as Turkey, Germany, Luxembourg, and Italy, the author emphasizes that such positive experience is of great importance for Ukraine. Such an approach is due to the fact that almost all of the countries in question are already current EU members or are seeking to join the Union. It is emphasized that their legislative acts are aimed at economically beneficial and adequate cooperation between the state and the taxpayer. The tendency to consolidate the institution under study at the State level is a confident step towards de-shadowing of the economy, both for small and large businesses. Conclusions and prospects for the development. The article also examines some peculiarities of tax amnesty regulation in Ukraine. In particular, the author refers to such a type of tax amnesty as a one-time (special) voluntary declaration of assets of individuals. It is emphasized that this declaration is characterized by the presence of its own legal mechanism. At the same time, such a mechanism is not identical to the mechanisms of tax amnesty in foreign countries. It is emphasized that the national tax legislation of Ukraine for the first time introduced a mechanism of alternative rates of fee for a one-time (special) voluntary declaration of assets of individuals. It should be noted that such an alternative is inextricably linked to the installment procedure, which differs significantly from the traditional mechanism of taxpayers’ tax debt installment.
Keywords: оподаткування; правове регулювання; податкова амністія; одноразове (спеціальне) добровільне декларування; декларування активів фізичних осіб; правовий механізм декларування; зарубіжний досвід; taxation; legal regulation; tax amnesty; one-time (special) voluntary declaration; declaration of assets of individuals; legal mechanism of declaration; foreign experience